The power of a positive No : how to say No and still get to Yes - Ury, William. (Bantam Books, 2007)
In today's world of high stress and limitless choices, the pressure to give in and say Yes grows ever greater, producing overload and overwork and eroding ethics. Every day we find ourselves in situations where we need to say No--to people at work, at home, and in our communities--because No is the word we must use to protect ourselves and to stand up for what matters to us. But the wrong No can also destroy what we most value by alienating and angering people--that's why saying No the right way is crucial. This book gives you a simple three-step method for saying a Positive No. It will show you how to assert and defend your key interests; how to make your No firm and strong; how to resist the other side's aggression and manipulation; and how to do all this while still getting to Yes.--From publisher description.